Effect of Leadership Style on School Performance of the Secondary Schools in Wadajir District, Mogadishu, Somalia - Omar, Abdulahi Mohamoud; Kavale, Stanley (IJRDO - Journal of Applied Management Science, 2016)
The purpose of this study was to assess the effect of leadership style on School performance of secondary schools in Wadajir District, Mogadishu- Somalia. The study utilized quantitative approach design based on descriptive in nature. The study was made using of a survey study research design and employing of administered questionnaires. The study targeted 10 schools with unit of enumeration consisting of 115 for the academic staff who were the principal, the deputy principal and teachers from the 10 schools. The study sampled 10 school leaders and 79 teachers using Slovene’s formula to form a total sample size of 89 respondents. The study implies that most secondary schools principals in Wadajir district had adopted Democratic and transformational leadership style compared to any type of other leadership style. Again results indicate that principals who are using democratic and transformational leadership style, their students and staff perform better than those who are using other types of leadership styles. The study recommended that the leaders of the schools should use the most appropriate leadership style that facilitates collective responsibility and consultative decision making with all stakeholders in the schools.